Loss of Opi3 causes a lipid imbalance that influences the virulence traits of Cryptococcus neoformans but not cryptococcosis - Lee, Christopher W. J.; Brisland, Anna; Qu, Xianya; Horianopoulos, Linda C.; Hu, Guanggan; Mayer, François L.; Kronstad, James W. (Frontiers in Cellular and Infection Microbiology, 2024)
The basidiomycete fungus Cryptococcus neoformans is a useful model for investigating mechanisms of fungal pathogenesis in mammalian hosts. This pathogen is the causative agent of cryptococcal meningitis in immunocompromised patients and is in the critical priority group of the World Health Organization fungal priority pathogens list. In this study, we employed a mutant lacking the OPI3 gene encoding a methylene-fatty-acyl-phospholipid synthase to characterize the role of phosphatidylcholine (PC) and lipid homeostasis in the virulence of C. neoformans. We first confirmed that OPI3 was required for growth in nutrient limiting conditions, a phenotype that could be rescued with exogenous choline and PC. Additionally, we established that loss of Opi3 and the lack of PC lead to an accumulation of neutral lipids in lipid droplets and alterations in major lipid classes. The growth defect of the opi3Δ mutant was also rescued by sorbitol and polyethylene glycol (PEG), a result consistent with protection of ER function from the stress caused by lipid imbalance. We then examined the impact of Opi3 on virulence and found that the dependence of PC synthesis on Opi3 caused reduced capsule size and this was accompanied by an increase in shed capsule polysaccharide and changes in cell wall composition. Further tests of virulence demonstrated that survival in alveolar macrophages and the ability to cause disease in mice were not impacted by loss of Opi3 despite the choline auxotrophy of the mutant in vitro. Overall, this work establishes the contribution of lipid balance to virulence factor elaboration by C. neoformans and suggests that host choline is sufficient to support proliferation during disease.